Sobre la distribución geográfica de las razas de Thinocorus rumicivorus y T. orbignyianus en las provincias de San Juan y Mendoza, Republica Argentina - Navas, Jorge R. (1997)
The presence of Thinocorus rumicivorus bolivianus is confirmed, from the extreme north of Argentina to the Northwest of Mendoza, where a pair was taken during the breeding season. The geographieal distribution of Thinocorus orbignyianus ingae is extended further to the south, in Northwestern Mendoza, and we show that the typical subspecies ranges from the south of Argentina to the south center of that province.